“All in One or (W)hole in One Repair” for Adult Total Brachial Plexus Palsy - Purushothaman, V.; Kumar, K. Vinoth; Ambat, Sabari Girish; Venkataswami, R. (Indian Journal of Plastic Surgery, 2021)
Background Total brachial plexus palsy (TBPP) accounts for nearly 50% of all brachial plexus injuries. Since achieving a good functional hand was almost impossible, the aim was settled to get a good shoulder and elbow function. It was Gu, who popularized the concept of utilizing contralateral C7 (CC7) with vascularized ulnar nerve graft (VUNG) to get some hand function. We have modified it to suit our patients by conducting it as a single-stage procedure, thereby trying to get a functional upper limb.Methods From 2009 to 2014, we had 20 TBPP patients. We feel nerve reconstruction is always better than any other salvage procedure, including free muscle transfer. We modified Gu's concept and present our concept of total nerve reconstruction as “ALL IN ONE OR (W)HOLE IN ONE REPAIR.”Results All patients able to move their reconstructed limbs independently or with the help of contralateral limbs. Three patients developed hook grip and one patient was able to incorporate limbs to do bimanual jobs. One important observation is that all the reconstructed limbs regain the bulk, and to a certain extent, the attitude and appearance looks normal, as patients no longer hide it or hang it in a sling.Conclusion Adult brachial plexus injury itself is a devastating injury affecting young males. By doing this procedure, the affected limb is not dissociated from the rest of the body and rehabilitation can be aimed to get a supportive limb.
Keywords: Contralateral C7; Superior ulnar collateral artery; Total Brachial Plexus Palsy; Vascularized Ulnar Nerve Graft